Lord of the flies [videorecording (DVD)] - Getty, Balthazar; Furrh, Chris; Pipoly, Danuel; Golding, William, 1911-1993 (Olive Films, 2015)
An adventure tale based on the classic novel by William Golding. When an aircraft carrying a group of military school cadets is forced to crash land in an uninhabited Pacific jungle, it is survival of the fittest, man against nature, and boy against boy as sides are drawn when the hunters become the hunted.